Durability tests of ball valve prototype with flowmeter operation - Rogula, Janusz; Romanik, G. (Zielona Góra: Uniwersytet Zielonogórski)
The results of the investigation of the prototypical ball valve are presented in this article. The innovation of the tested valve is a ball with a built-in measuring orifice. The valve has been subjected to durability tests. Leakage under three temperatures: ambient, -30 degress C and +100 degress C was analyzed. Sealing elements of the valve were tested for roughness and deviation of shape before and after the cycles of operation.
Keywords: friction; leakage; ball valve; prototype